Big Book “Aku Anak Indonesia” to Stimulate Religious Moderation in Early Childhood - Ni Luh Drajati Ekaningtyas; Ni Nyoman Sinar Widia Swari (Journal of Psychology and Instruction, 2023)
Cases of violence and discrimination in Indonesia are still dominated by religion-based conflicts, so it is important to internalize religious moderation from an early age. Stimulation in early childhood requires special learning media that suit their characteristics and developmental needs, one of which is a big book with attractive and colorful pictures. However, there is no big book that has been specifically developed to stimulate religious moderation for early childhood. Therefore, this study aims to develop a a valid and appropriate big book with entitled "Aku Anak Indonesia" to stimulate religious moderation in early childhood. This study used Borg&Gall's research and development method which consisted of 10 research procedures. The subjects in this study were 90 students and 7 teachers in Kindergarten. Data collection was carried out using questionnaires, interviews, observation, and documentation. Data analysis was carried out qualitatively and quantitatively. The results of the data analysis illustrate that the developed big book "Aku Anak Indonesia" is very valid (98%) and feasible (94.05%) to stimulate religious moderation in early childhood. Early childhood increasingly understands concepts and is able to apply religious moderation in daily life after stimulation with big books.